Why people buy fashion - Tseëlon, Efrat; Guedes, Maria Graça (Henry Stewart Talks, 2014)
The fashion market, Fashion value, Why does fashion change?, How do fashion trends emerge?, Counter-culture anxiety, Cultural models of idealised reality, Cultural conflict between mainstream and margin, Appropriation of group specific symbols, Fashion diffusion theories, Dynamics of fashion adoption, Diffusion of innovation, Contemporary fashion opinion leaders, From hierarchical to fragmented system, From group pressure to individuality, Change of consumer focus, Decentralisation of fashion, Decline of sartorial rules, Young fashion consumers, Silver fashion consumers, The after-effects of the economic downturn, Western consumer mega trends, Technology-driven retailing, Mature and developing markets, The Western European market, Micro level explanations, Macro level explanations